Design and Development of a Web-Based Information System Using Agile Methodology for PKBM Satria - Bintang Cahaya Purnama; Sisilia Thya Safitri (Telkom University, 2025)
PKBM Satria is a non-formal educational institution that still conducts its student registration and provision of learning materials manually. The main problems include incomplete data, swapped attachments, the risk of document loss, and limited learning access due to shared classroom usage. This research aims to develop a web-based information system using the Agile method to overcome these issues. The system's primary features include online registration, management of student and teacher data, and online learning. Black Box testing showed that all features function properly. The User Acceptance Test (UAT) results indicate the system is well-accepted by its users: admins gave an average score of 80% (very good), teachers scored 80.4% (very good), and students scored 67.1% (good). This study proves that implementing the Agile method is effective in producing an adaptive digital solution for non-formal education.